The forecasting of manpower requirements - United States (Washington, D.C. : U.S. Dept. of Labor, Bureau of Labor Statistics, 1963)
The manual is intended to serve as a guide in forecasting the manpower requirements associated with economic development. The method outlined is based largely on United States experience.
Includes bibliographical references: p. 77-94.
rpm 27/02/2018
Loans
Keywords: Labor supply; Employment forecasting